A review study for the application of heat pipe and nano-enhanced PCM cooling methods on solar concentrated photovoltaic panels: Sate-of-the-art designs, outcomes and future trends - Okulu, Damla; Selimefendigil, Fatih; Öztop, Hakan Fehmi; Baysal, Esref (Elsevier, 2025)
Concentrated photovoltaic panels (CPVs) appear as designs that can provide a solution to the energy crisis that exists today. However, performance degradation caused by overheating of CPVs has not yet been literally resolved. In this context, in order to solve this problem, different cooling methods are applied to CPVs and developments are being made. This research specifically focuses on nano-enhanced PCM (phase change material) and heat pipe applied to CPV. Different designs of these cooling methods enable cell temperature reduction in CPV and thus improvements in electrical power output. In CPV/nano-enhanced PCM studies, parameters such as thickness and nanoparticle type and ratio as well as inclination angle and fin usage were also effective on thermal performance. Metal oxide material group (CuO, MgO, SiO2, ZnO, TiO2, SiO2) has been predominantly preferred as nanoparticles, but there are also studies using materials such as graphene and copper. In addition, comparative analysis of pure PCM and nano-enhanced PCM shows that nanoparticle addition into PCM results in improved electrical power of CPV. It is supported by studies that nanoparticle loading rate also has an effect on performance. When considering CPV/heat pipe design, working fluid, heat pipe length and inclination angle, and liquid loading ratio appear as significant parameters. Improvement in CPV performance was achieved with the increase in heat pipe length. Performance changes occurred in CPV with different working fluids. It is seen that the use of acetone and nanofluid (Ag-water) provides higher CPV electrical power compared to water. In this study, effects of various parameters of both the nano-enhanced PCM and the heat pipe on CPV were comprehensively discussed. Different designs of nano-enhanced PCM and heat pipe applied in the literature were investigated. The effective parameters of these cooling methods and the most advanced model designs obtained by optimizing these parameters were analyzed. Studies conducted in this direction have shown remarkable increases in PV efficiency. In the future, there is potential to obtain state-of-the-art CPV systems in the scenario where comparative analyses of PCM groups (organic, inorganic and eutectic) or different heat pipe designs (flat plate, pulsating, loop, tubular etc.) are performed.
Keywords: PV cooling; CPVs; Nano-PCM; Nanoparticle; Heat pipe